The Influence of Posyandu Cadres Credibility on Community Participation in Health Program - Dewi, Retasari; Anisa, Renata (Universitas Semarang, 2018)
The foremost guard of health services in Indonesia is in the Puskesmas with its integrated health service post called Posyandu. Posyandu West Bandung Regency has several times won the champion as the best Posyandu in West Java and National level. This achievement was achieved because the role of Posyandu cadres in the area. Based on the background, this study examines how much influence the credibility of Posyandu cadres to public participation in health programs using the Credibility Theory, this study uses an explorative quantitative approach. Result of this research with Pearson correlation analysis showed that credibility Posyandu cadres have an effect on society participation in health program, with r = 0.0006. While Posyandu cadre expertise is quite influential with r = 0.0006; the character of trusted cadres is also influential with r = 0.0006; and the appeal of Posyandu cadres is quite influential with r = 0.0005.